2018
DOI: 10.2807/1560-7917.es.2018.23.39.1700548
|View full text |Cite
|
Sign up to set email alerts
|

The shift in rabies epidemiology in France: time to adjust rabies post-exposure risk assessment

Abstract: The epidemiology of rabies in France and western Europe has changed during the past 22 years. In France, rabies in non-flying terrestrial mammals was declared to be eliminated in 2001, and the risk of rabies is now limited to contact with bats, rabid animals illegally imported from rabies-enzootic countries and traveller exposure in enzootic areas. We analysed the epidemiology of rabies in France from 1995 to 2016, describing and analysing data on human rabies surveillance as well as data on post-exposure prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Therefore, the epidemiology of rabies in Western Europe has changed during the past 22 years. As such, Parize et al (2018) recently reported that in France, which eliminated rabies in non-flying terrestrial mammals in 2001, the risk of rabies is now limited to contact with bats, rabid animals illegally imported from rabies-enzootic countries, and traveller exposure in enzootic areas. This may explain why 2017 monitoring data from bats were mainly reported by Western and Northern European MS countries and why during the last 5 years the number of reported tested bats in Central and Western Europe increased.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the epidemiology of rabies in Western Europe has changed during the past 22 years. As such, Parize et al (2018) recently reported that in France, which eliminated rabies in non-flying terrestrial mammals in 2001, the risk of rabies is now limited to contact with bats, rabid animals illegally imported from rabies-enzootic countries, and traveller exposure in enzootic areas. This may explain why 2017 monitoring data from bats were mainly reported by Western and Northern European MS countries and why during the last 5 years the number of reported tested bats in Central and Western Europe increased.…”
Section: Discussionmentioning
confidence: 99%
“…Every patient received a WHO-recommended vaccine regimen but only 7 of the 18 patients with category III exposures had RIG administration. This small proportion could not entirely be explained by the initiation of PEP abroad (3 patients) and may reflect the insufficient knowledge of WHO recommandations among French health care workers [16]. An inadequate immune response after PEP has been documented in 6 non-HIV immunocompromised patients out of 28 attending 2 French Antirabies Clinics.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined data on individuals seeking care at an Anti‐Rabies Clinic (ARC) after a bat exposure in metropolitan France from 2003 to 2016. In France, primary healthcare management of individuals seeking care after a potential rabies exposure is delivered through an official national network of 70 clinics located throughout the country (Parize et al, 2018). The NRCR collects anonymous data on each individual seeking care in these centres through online standardized report forms completed by Anti‐Rabies Clinic practitioners (Vaccilab/Voozanoo, Epiconcept, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…Bats are the recognized reservoirs for the majority of lyssaviruses in the world (Banyard, Evans, Luo, & Fooks, 2014; Calisher, Childs, Field, Holmes, & Schountz, 2006). Bat exposures remain the only possible source of autochthonous lyssavirus transmission to humans since the elimination of rabies in dogs in the 20th century and in terrestrial wild animals at the beginning of the 21st century in Western Europe (Parize, Dacheux, Larrous, & Bourhy, 2018). Furthermore, as the European Union objective is to eradicate rabies in terrestrial mammals by 2020, bats will soon be the only reservoir of lyssavirus in all European Union member states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation